Soil chemical characteristics of native pasture affected by liquid swine manure - Ceretta, Carlos Alberto (2003)
Pig slurry is a fertilizer but its improper use can contaminate water and soil. The objectives of this study were to determine soil chemical attributes affected by liquid swine manure applied on native pasture and to evaluate the agronomic and environmental impacts of its use. An experiment with liquid swine manure application on native pasture was carried out from November 1995 to November 1999, in an area nearby a swine production place in Paraíso do Sul county, State of Rio Grande do Sul, Brazil, to evaluate the soil chemical attributes. The liquid swine manure application rates were: 0, 20 and 40 m3 ha-1, applied every 45 to 60 days. Right before each manure application, the forage was mowed and taken out. The liquid manure application on natural grass field every 45 to 60 days cause a high addition of soil chemical elements, specially P, Ca and Mg. The reduction of Al saturation may improve soil environment to plant growth, however, the K content should be monitored, because under grazing the latter could decrease. The system should have high N leaching in nitrate form, because, despite heavy N application through manure, the soil N content remains almost the same. This, in turn, could become an environmental problem, as long as one consider a high P content at surface also as potential water pollutant.